An Unknown Translation of the Czech Book of "Lucidář" into Ruthenian (1563) and Its Oldest Copy of the Late Sixteenth-Century - Temchin, Sergei (Senoji Lietuvos literatūra, 2021)
The article presents an unknown translation of the Czech book of Lucidář into Ruthenian preserved in two Cyrillic manuscript copies of the late sixteenth and the seventeenth century. The latest copy ends with the date 1563, which does not correspond to the age of the copy itself and therefore should be considered as indicating the time of the translation. Particular attention is paid to clarifying the dating of the earlier manuscript copy describing its linguistic features, indicating the northern (‘Belarusian’) type of its Ruthenian language, and identifying rare phonetic, orthographical, and morphological features, which indicate a possible southern (‘Ukrainian’) origin of the previous antegraphs. An argument is made in favour of the fact that the scribe of the earliest Cyrillic manuscript copy was a Catholic. The earliest manuscript copy of the late sixteenth century, kept in P. N. Dobrokhotov’s St. Petersburg collection (No. 18, fol. 167–174), is published in the appendix.Previously, two other Ruthenian translations of the Czech book of Lucidář were known, one of which was made around the middle of the sixteenth century in the kingdom of Hungary or Poland (the text identifies the ‘Dalmatian’ Mount Olympus with the Tatras), and the other was produced in 1636 from a nonextant Czech printed edition (*Olomouc, 1622).
Keywords: Grand Duchy of Lithuania; Cyrillic manuscripts; Ruthenian language; translations from Czech; Lucidarius